Penerapan Model Pembelajaran Picture And Picture Untuk Meningkatkan Hasil Belajar Geografi Pada Materi Siklus Hidrologi Siswa Kelas X SMA Negeri Alkhairat Kota Ternate - Andi Suaema (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to improve geography learning outcomes through the application of the picture and picture learning model. The data needed in this study is data on teacher and student activities and learning outcomes. This type of research is Classroom Action Research (CAR) or in English is called Classroom Action Research using quantitative research methods. Data collection techniques used are observation sheets and learning achievement tests. The use of the picture and picture learning model shows a significant increase in learning outcomes in accordance with KKM standards. The results of the evaluation of the first cycle showed that the average value was 71.30 and in the second cycle there was an increase with an average value of 81.73.